English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-15 03:07:07 · 4 answers · asked by norman 1 in Science & Mathematics Mathematics

4 answers

To make things easier, multiply both sides by 6 first (2*3):

6[(7x-5)/2 - 4] = 6[(5x+2)/3]
3(7x-5) - 6(4) = 2(5x+2)
21x - 15 - 24 = 10x + 4
11x - 39 = 4
11x = 43
x = 43/11

2006-12-15 03:12:45 · answer #1 · answered by Jim Burnell 6 · 1 0

[(7x - 5) / 2] - 4 = (5x + 2) / 3

7x - 5 / 2 - 4 = 5x + 2 / 3

6(7x - 5 / 2) - 6(4) = 6(5x + 2 / 3)

3 (7x - 5) - 24 = 2(5x + 2)

21x - 15 - 24 = 10x + 4

21x - 39 = 10x +4

21x - 39 - 10x = 10x + 4 - 10x

11x - 39 = 4

11x - 39 + 39 = 4+ 39

11x = 43

11x/11 = 43/11

x = 43/11

x = 3 10/11

The answer is x = 3 10/11

- - - - - - - -s-

2006-12-15 11:33:42 · answer #2 · answered by SAMUEL D 7 · 0 0

GCF(2, 1, 3)= 6
3{[(7x-5)] -6(4) = 2(5x+2)}
21x - 15 - 24 = 10x + 4
21x - 10x = 4 + 39
11x = 43
x = 43/11
Then, {x E R | x = 43/11}.
<>

2006-12-15 11:11:39 · answer #3 · answered by aeiou 7 · 0 2

(7x-5)(-2)=(5x+2)/3
-6(7x-5)=5x+2)
=42x+30=5x+2
adding -5x-2
37x+28=0
adding -28
37x=-28
dividing by 37
x=-28/37

2006-12-15 11:14:53 · answer #4 · answered by raj 7 · 0 1

fedest.com, questions and answers